Design of AsLOV2 domain as a carrier of light-induced dissociable FMN photosensitizer - Felčíková, Kristína; Hovan, Andrej; Polák, Marek; Loginov, Dmitry S; Holotová, Veronika; Díaz, Carlos; Kožár, Tibor; Lee, One-Sun; Varhač, Rastislav; Novák, Petr; Bánó, Gregor; Sedlák, Erik (Protein science, 2024)
Flavin mononucleotide (FMN) is a highly efficient photosensitizer (PS) yielding singlet oxygen (1 O2 ). However, its 1 O2 production efficiency significantly decreases upon isoalloxazine ring encapsulation into the protein matrix in genetically encoded photosensitizers (GEPS). Reducing isoalloxazine ring interactions with surrounding amino acids by protein engineering may increase 1 O2 production efficiency GEPS, but at the same time weakened native FMN-protein interactions may cause undesirable FMN dissociation. Here, in contrast, we intentionally induce the FMN release by light-triggered sulfur oxidation of strategically placed cysteines (oxidation-prone amino acids) in the isoalloxazine-binding site due to significantly increased volume of the cysteinyl side residue(s). As a proof of concept, in three variants of the LOV2 domain of Avena sativa (AsLOV2), namely V416C, T418C, and V416C/T418C, the effective 1 O2 production strongly correlated with the efficiency of irradiation-induced FMN dissociation (wild type (WT) < V416C < T418C < V416C/T418C). This alternative approach enables us: (i) to overcome the low 1 O2 production efficiency of flavin-based GEPSs without affecting native isoalloxazine ring-protein interactions and (ii) to utilize AsLOV2, due to its inherent binding propensity to FMN, as a PS vehicle, which is released at a target by light irradiation.
Keywords: miniSOG; aminokyseliny; Flavin Mononucleotide; LOV2 domain; proteinové domény; flavin cofactor; Binding Sites; fotosenzibilizující látky; flavinmononukleotid; singlet oxygen; vazebná místa; Protein Domains; genetically encoded photosensitizers; flavoproteiny; Photosensitizing Agents; Flavoproteins; Amino Acids